The pathogenesis of iodide mumps: A case report. Issue 47 (November 2017) - Zhang, Guilian; Li, Tao; Wang, Heying; Liu, Jiao
Abstract: Relation: Iodide mumps is an uncommon condition, induced by iodide-containing contrast, and is characterized by a rapid, painless enlargement of the bilateral or unilateral salivary gland. At present, the pathogenesis of iodide mumps is not yet clear. It may be related to an idiosyncratic reaction, a toxic accumulation of iodine in the gland duct, or renal function damage leading to an iodine excretion disorder. This paper reports the clinical manifestations and magnetic resonance imaging results of one case of iodide mumps, which occurred after digital subtraction angiography. Patient concerns: A 66-year-old Chinese man presented to our department with a 1-month speech barrier and 1 day of vomiting. He had the history of high blood sugar, the history of high blood pressure and the history of Vitiligo. He had no history of allergies and had never previously received iodide-containing contrast. His renal function and other laboratory examinations were normal. During the digital subtraction angiography (DSA), the patient received approximately 130 mL of nonionic contrast agent (iodixanol). Five hours postsurgery, the patient experienced bilateral parotid enlargement with no other discomfort, such as pain, fever, skin redness, itching, hives, nausea, vomiting, or respiratory abnormalities. Diagnoses: We thought the diagnosis was iodide mumps. Intervention: Intravenous dexamethasone (5 mg) was administered. Outcome: 20 hours post-DSA, after which the bilateral parotid shrunk. By 4 days postsurgery, the patient's bilateral parotid had recovered completely. Lessons: We found no obvious abnormal sequence signal in diffusion magnetic resonance imaging or the corresponding apparent diffusion coefficient. Our findings suggest that vasogenic edema may play an important role in the pathogenesis of iodide mumps.